2020
DOI: 10.1080/15592294.2020.1750213
|View full text |Cite
|
Sign up to set email alerts
|

The epitranscriptomic writer ALKBH8 drives tolerance and protects mouse lungs from the environmental pollutant naphthalene

Abstract: The epitranscriptomic writer Alkylation Repair Homolog 8 (ALKBH8) is a transfer RNA (tRNA) methyltransferase that modifies the wobble uridine of selenocysteine tRNA to promote the specialized translation of selenoproteins. Using Alkbh8 deficient ( Alkbh8 def ) mice, we have investigated the importance of epitranscriptomic systems in the response to naphthalene, an abundant polycyclic aromatic hydrocarbon and environmental toxicant. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…For example, mouse KO of the tRNA modification enzyme Alkbh8 caused mismodification of several distinct tRNA isoacceptors at the critical wobble uridine position, but gave no overt phenotype 29 , 30 . However, later studies showed defects in selenoprotein synthesis and stress tolerance in the Alkbh8 KO mice 31 , 32 , and it was recently reported that homozygous inactivating mutations in the human ALKBH8 gene causes intellectual disability and general developmental delay 33 . Likewise, more detailed studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mouse KO of the tRNA modification enzyme Alkbh8 caused mismodification of several distinct tRNA isoacceptors at the critical wobble uridine position, but gave no overt phenotype 29 , 30 . However, later studies showed defects in selenoprotein synthesis and stress tolerance in the Alkbh8 KO mice 31 , 32 , and it was recently reported that homozygous inactivating mutations in the human ALKBH8 gene causes intellectual disability and general developmental delay 33 . Likewise, more detailed studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that UGA/Sec re-coding in Gpx1 is not (always) sensitive to full mcm 5 U modification [ 59 ]. So, we wonder whether one could look at the available data in another way: formation of mcm 5 Um 34 in tRNAs is not unique for tRNA [Ser]Sec , but may represent a general mechanism to cope with oxidative stress [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epitranscriptomic base modifications have become an interesting topic of research and review, particularly in the animal system ( Meyer et al, 2012 ; Carlile et al, 2014 ; Fu Y. et al, 2014 ; Dominissini et al, 2016 ; Peer et al, 2017 ; Angelova et al, 2018 ; Arribas-Hernandez et al, 2018 ; Khoddami et al, 2019 ; Leonardi et al, 2020 ). Now, the epitranscriptomic modifications in plants like Arabidopsis ( Luo et al, 2014 ; Wan et al, 2015 ; Shen et al, 2016 ; Zuber et al, 2016 ; Cui Q. et al, 2017 ; David et al, 2017 ; Duan et al, 2017 ), rice ( Li Y. et al, 2014 ), maize ( Luo et al, 2019 ; Miao et al, 2019 ), and tomato ( Zhou et al, 2019 ) are also being studied.…”
Section: Introductionmentioning
confidence: 99%